202k views
2 votes
ANSWER THIS CORRECTLY AND I WILL 5 STAR U AND GIVE U POINTS AND THANK YOU

IF NOT ME AND MY CLASS WILL REPORT YOU FOR WRONG ASNWERS AND GIVE U ONE STAR

HELP ME OUT PLS :))
HAPPY THANKSGIVING ALL!

ANSWER THIS CORRECTLY AND I WILL 5 STAR U AND GIVE U POINTS AND THANK YOU IF NOT ME-example-1
User Ewoud
by
5.6k points

2 Answers

6 votes

Answer:

C.

Explanation:

A.) y - 1 = -2(x - 3)

y - 1 = -2x + 6

y = -2x + 6 + 1

y = -2x + 7

B.) y - 1 = -2(x + 3)

y - 1 = -2x - 6

y = -2x - 6 + 1

y = -2x - 5

C.) y + 1 = -2(x - 3)

y + 1 = -2x + 6

y = -2x + 6 - 1

y = -2x + 5

D.) y + 1 = -2(x + 3)

y + 1 = -2x - 6

y = -2x - 6 - 1

y = -2x - 7

User Danesha
by
5.9k points
0 votes

Answer:

C

Explanation:

given:

m= -2 and (3, -1)

point-slope form: y-y1= m(x-x1)

y - (-1) = -2(x-3)

y + 1 = -2(x-3)

User Amel
by
6.2k points